Nursing care of a 45 year-old patient after vaginal hysterectomy in a hospital environmet - Ciechacka, Maria; Świst, Sonia; Pawełko, Agnieszka (Journal of Education, Health and Sport, 2025)
Uterine fibroids are a common gynecological condition that can significantly reduce the quality of life of women and lead to health complications. They are a significant health problem related to both the physical health and mental well-being of patients. Symptoms of fibroids can significantly worsen the quality of life of women, contribute to low mood, deterioration of interpersonal relationships and a decrease in professional efficiency, which can limit the ability to perform social and professional roles. Effective diagnosis and treatment are key elements of patient care. After vaginal hysterectomy, patients require holistic nursing care that supports not only the healing process but also helps to regain emotional balance after the procedure. High-quality care has a significant impact on a faster recovery and improved mental well-being of the patient.